Apheresis in Neurological Disorders - Dorst, Johannes (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Apheresis refers to an extracorporeal therapy which aims at removing pathological constituents from the patients' blood. Due to the development of new techniques as well as the discovery of novel autoimmune antibodies, it is increasingly recognized as an important therapeutic option for a variety of autoimmune-mediated neurological disorders, including multiple sclerosis, myasthenia gravis, autoimmune encephalitis, Guillain-Barré syndrome, and many others. Therapeutic plasma exchange (TPE) constitutes the standard method of apheresis for most indications, while immunoadsorption (IA) offers a more specific, low-risk alternative. Both methods aim at removing auto-antibodies from the blood. Evidence for most neurological diseases is still low. Interestingly, more recent developments suggest that apheresis is not limited to the removal of autoantibodies but may also be useful in neurodegenerative and possibly even in acute vascular disorders.